Agronomic characteristics and rain use efficiency of sorghum in a semiarid region (Research, Society and Development, 2020)
Sorghum culture highlighted in animal nutrition because it allows its cultivation of green conservation as silage. This study aimed to evaluate the divergence of agronomic and productive characteristics of 32 sorghum cultivars in the semiarid region. The randomized block design with three replications was used. It was evaluated the dry matter percentage (DM), fresh matter production (FMP) and dry matter production (DMP); stem proportion, panicle, and leaf blade in the plant DM; plant height, nº plants ha-1, stem diameter, leaf number, leaves and panicles length; rain use efficiency (RUE) in kg MS ha-1 mm-1, and water accumulation (WA) in kg ha-1 and kg ha-1 mm-1. The data were analyzed using the Scott-Knott procedure at a 5% significance level. The FMP and DMP showed the formation of two distinct groups, which may be crucial in choosing a more productive cultivar. Moreover, cultivar 17 stood out for presenting high leaf blade participation while cultivars 9, 19, 23, 24, and 32 in panicle participation in DM, which is considered nutritionally better due to higher digestibility than the stem. Besides, for the RUE and WA, two distinct groups were also formed, which can be great to determine cultivars that have higher xerophilic potential, and thus use them for the production of silage in semi-arid conditions. Experimental cultivars showed greater results than those commercials. Studies that evaluate the animal performance of cultivars (3, 6, 9, 17, 19, and 31), could be conducted to prove their nutritional values since these cultivars stood out for presenting interesting productive characteristics.